2020
DOI: 10.1093/infdis/jiaa173
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Mucosal-Associated Invariant T Cells in Tuberculosis Patients and Healthy Mycobacterium tuberculosis-Exposed Controls

Abstract: Background In human blood, mucosal-associated invariant T (MAIT) cells are abundant T cells that recognize antigens presented on non-polymorphic major histocompatibility complex-related 1 (MR1) molecules. The MAIT cells are activated by mycobacteria, and prior human studies indicate that blood frequencies of MAIT cells, defined by cell surface markers, decline during tuberculosis (TB) disease, consistent with redistribution to the lungs. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Wong et al (17) found a trend toward decreased frequency of CD161 hi CD8 + T cells in PBMCs from LTBI compared with controls in a TB-endemic African setting. Other studies have found no difference in MAIT frequencies in LTBI compared with TB neg, or even an increase (16,18). These contradictory results may be explained by variations in M. tuberculosis exposure rates in endemic versus nonendemic TB areas, how well the latent infection is controlled, as well as a difference in how MAIT populations were defined.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Wong et al (17) found a trend toward decreased frequency of CD161 hi CD8 + T cells in PBMCs from LTBI compared with controls in a TB-endemic African setting. Other studies have found no difference in MAIT frequencies in LTBI compared with TB neg, or even an increase (16,18). These contradictory results may be explained by variations in M. tuberculosis exposure rates in endemic versus nonendemic TB areas, how well the latent infection is controlled, as well as a difference in how MAIT populations were defined.…”
Section: Discussionmentioning
confidence: 88%
“…One of the most frequent nonclassically restricted T cell populations in the blood are MR1-restricted T cells, which decrease in frequency in active TB (14,15). For LTBI, there have been contradicting results regarding the frequency of MAITs in PBMCs (14,(16)(17)(18). MR1-restricted T cells represent a significant fraction of CD8 + and CD4 -CD8 -T cells in peripheral blood (19,20).…”
mentioning
confidence: 99%
“…Next, we wanted to measure the frequency of DAT 2 -reactive T cells in a cohort of 150 human subjects 27 , 28 to determine if there is an Mtb infection or disease-associated expansion of DAT-specific T cells. PBMCs were isolated from 50 Peruvian individuals with active tuberculosis (TB) before the start of anti-TB drug treatment.…”
Section: Resultsmentioning
confidence: 99%
“…MAIT cells are multifaceted in their functional response to infections and in maintaining homeostasis, also contributing to tissue repair and wound healing 3 . In the context of M. tb , human blood MAIT cell frequencies are reportedly reduced during active infection, 4 suggestive of circulating MAIT cell migration into the tissues, although a recent large cohort study disputes this finding 5 . Human MAIT cells also secrete interferon‐gamma when cultured with M. tb ‐infected antigen‐presenting cells 4 .…”
Section: Figurementioning
confidence: 99%
“…3 In the context of M. tb, human blood MAIT cell frequencies are reportedly reduced during active infection, 4 suggestive of circulating MAIT cell migration into the tissues, although a recent large cohort study disputes this finding. 5 Human MAIT cells also secrete interferon-gamma when cultured with M. tb-infected antigen-presenting cells. 4 Similarly, in mice, MAIT T-cell receptor transgenic cells secrete interferongamma in response to BCG and can inhibit its intracellular growth.…”
mentioning
confidence: 99%